A Public Encounter in New York City A Phenomenological View on a Sobering Experience - Oh, Joong-Hwan. (Cham : Springer International Publishing : Imprint: Palgrave Macmillan, 2023)
This book examines the essence of a particular personal experience within a New York City public space. The principal approach, both theoretical and methodological, is the phenomenological perspective, an in-depth study of such a surprising experience in the real world from the first-person point of view. The book introduces a new concept of "the situated self," that is, the whole entity of the respondent's subjective world about his or her particular urban experience in public. It is one's "being-in-the-word" or lived experience in the real world. Another important feature of "the situated self" is its comprehensive constitution of all certain human traits, perceptions, emotions, bodily sensations, cognition, and behavioral reaction, and their close situational connectivity to one another. By implication, this public experience of "the situated self" is a common denominator shared among regular users of New York City public spaces for making their city life with urban strangers more routinized, predictable, tolerant, and civic.
1. Framing an Unanticipated Public Experience in New York City -- 2. The Public Setting of an Unexpected Experience in New York City -- 3. The Essence of a Public Experience in New York City: The Situated Self in Public I -- 4. A Public Experience in New York City from the Lens of a Victim: The Situated Self in Public II -- 5. A Public Experience in New York City from the Lens of a Bystander: The Situated Self in Public II -- 6. The Present Style of Public Life in New York City -- 7. Conclusions and Implications.
Keywords: Sociology, Urban; Sociology; Human geography; Urban Sociology; Sociological Theory; Human Geography